Osteoclast-like multinucleated giant cells reinforce polycaprolactone grafts - Einarsson, Halldór Bjarki; Mortensen, Anders Frisk; Nielsen, Morten Schallburg; Chen, Menglin; Nielsen, Søren Roesgaard; Kraft, David Christian Evar; Jensen, Jonas; Bjerre, Mette; Andersen, Morten Nørregaard; Nygaard, Jens Vinge; Bünger, Cody Eric; Vorup-Jensen, Thomas (Frontiers in Immunology, 2025)
Successful application of advanced engineered materials in osteoplasty requires a biological understanding of the recipient reaction. The immune system acts like a double-edged sword by maintaining targeted tissue and rejecting grafts. Nevertheless, even for promising graft materials such as polycaprolactone, insights on contact with immune cells have been restricted due to lacking quantitative assays. Here, we show that polycaprolactone graft sites after cranioplasty are dominated by an immature type of multinucleated giant cells, probably derived from transmigrating peripheral monocytes. The cells interact with the polycaprolactone through extensive pseudopodia formation and localized polymer dissolution. Dynamic mechanical analysis revealed osteoclast-like cells, derived in vitro from primary human monocytes, reinforce polycaprolactone by depositing a CD18 integrin-rich attachment matrix. Our findings give a new perspective on immune cells’ beneficial and detrimental functions in graft lesions, guiding therapy with better graft designs.